PROTOCOLO DE CONDUTAS MÉDICAS EM DERMATOLOGIA APLICADO ÀS GESTANTES - Pereira, Michelle Pimentel Magalhães (2024)
Pregnancy is a physiological state accompanied by significant hormonal and metabolic changes, resulting in various bodily alterations, including dysfunctions of the skin and its appendages. Objectives: To describe dermatological changes and associate the findings with sociodemographic conditions, nutritional and anthropometric status, pre-existing and gestational diseases; and to develop a medical protocol to address the dermatological changes observed in pregnant women. Methodological Approach: A methodological study conducted in sequential stages: a literature review on dermatological changes in pregnant women, data collection from March to June 2024 in health units in Santa Maria, RS, with a sample of third-trimester pregnant women. The study employed a cross-sectional, analytical, and quantitative design. In this stage, sociodemographic, obstetric, and dermatological information was collected from pregnant women attending public health units. The data were analyzed using SPSS software, and the results and discussions served as the basis for developing a medical protocol. This protocol, aligned with Brazilian guidelines, includes the definition of the topic, title, presentation, introduction, objectives, target population, included approaches, implementation indicators, and references. It is intended for primary health care professionals conducting prenatal consultations. Results: A total of 100 pregnant women were evaluated, with a mean age of 26.35 ± 6.49 years and an average income of 1.68 ± 0.72 Brazilian minimum wages. Among the participants, 30 (30%) had pre-existing health conditions, while 64 (64%) reported no obstetric history. The predominant phototype was II, representing 41 (41%) of the pregnant women, and the most common dermatoses were hyperpigmentation and striae. A significant correlation was observed between pre-gestational BMI and the number of dermatological changes, with higher frequencies among obese pregnant women. The mean number of dermatological changes in underweight pregnant women was 2.75 ± 0.95, in those with normal weight 2.50 ± 1.34, in overweight women 3.16 ± 1.34, and in obese women 3.55 ± 1.21 (p = 0.014). Additionally, 82.8% of patients with striae had inadequate gestational weight gain. Based on these data and the literature review, a protocol for dermatological care in pregnant women was created, targeting healthcare professionals. This protocol classifies pathologies into groups and includes general information, clinical presentation, and therapeutic options for each condition, as well as recommendations adapted to the reality of patients in the public health system. Final Considerations: The analysis of pregnant women revealed socioeconomic vulnerability and a high incidence of comorbidities, such as metabolic disorders. The most prevalent dermatoses were striae and vascular changes, particularly among obese pregnant women. The development of a dermatological care protocol, based on field research and scientific evidence, focused on comprehensive and safe care, considering therapeutic limitations and the need for weight control. It aims to standardize practices, prevent complications, and promote a multidisciplinary approach, ultimately improving care for pregnant women in the public health system.